Prevalensi Nematoda Parasit pada Pertanaman Pisang di Daerah Istimewa Yogyakarta - Siwi Indarti; Bambang Rahayu TP; Siti Subandiyah; Lilis Indarti (Universitas Gadjah Mada, 2011)
A study to determine the prevalence and distribution of plant parasitic nematodes associated with banana was undertaken in banana growing areas at four districts (Bantul, Gunung Kidul, Kulon Progo, and Sleman) of Yogyakarta Special Province. Seven genera of plant parasitic nematodes were found on these area: Criconemoides, Helicotylenchus, Hoplolaimus, Meloidogyne, Pratylenchus, Radopholus, and Rotylenchulus. Genera Hoplolaimus and Meloidogyne were distributed at all districts and occurring in soil and root samples of banana cultivars, Ambon, Kepok, Koja, Klutuk, Raja, Tanduk, and Uter, respectively. Four genera, Hoplolaimus, Meloidogyne, Pratylenchus, and Radopholus were dominant and were found with high level of population than the others on each district. Pratylenchus mostly was found on banana cv Kepok with average population 348,2–2057,3 nematodes on total samples of 5g banana root and 100g soil.